2007
DOI: 10.5194/aab-50-520-2007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding with low-protein feed mixes on the growth and slaughter value of young male Pharaoh quails

Abstract: Experimental material consisted of one-day Pharaoh quail chicks, which were separated into three experimental groups. The birds of group I received a fodder, the nutritive value of which was consistent with recommended feeding standards for growing quails, whereas for those of group II and III the protein level was lowered in all feed mixes appropriated for the whole rearing period. During the experiment, individual body weight, feed consumption, and bird deaths and their health culling were controlled. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
3
9
1
Order By: Relevance
“…Similar L* values (43.12-46.66) were obtained for game pheasants by Kuźniacka et al [20] and markedly lower (33.69-35.42) in quail [32]. Meanwhile, Bianchi and Fletcher [10] found lower L* values (darker colour) in chickens with thicker breast muscles and higher rate of growth.…”
Section: Discussionsupporting
confidence: 65%
“…Similar L* values (43.12-46.66) were obtained for game pheasants by Kuźniacka et al [20] and markedly lower (33.69-35.42) in quail [32]. Meanwhile, Bianchi and Fletcher [10] found lower L* values (darker colour) in chickens with thicker breast muscles and higher rate of growth.…”
Section: Discussionsupporting
confidence: 65%
“…It was 0.3% in 35-day-old birds and 1.1% in 45-day-old birds. In an earlier study (Tarasewicz et al, 2007), the proportion of testicles in 42-day-old male Pharaoh quail was greater (2.07%) than in our study.…”
Section: Resultsmentioning
confidence: 62%
“…Younger quail were characterized by significantly lower testicular weight, which was 0.4 g in 35-day-old birds and 1.9 g in 45-day-old birds. Tarasewicz et al (2007), who investigated the effect of giving a low-protein feed on the growth and slaughter value of Pharaoh quail, found higher testicular weight in 42-day-old males (3.4 g). The proportion of liver (Table 7) was lower in birds aged 35 days compared to 45-day-old birds (2.2 and 2.4%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gheisari et al (2011) indicated that increasing dietary CP in the different stages of growth from very low, medium and high levels significantly (p#0.05) increased LBW and BWG of growing Japanese quails. Contradicting results were reported by Tarasewicz et al (2007) found that, quail fed diet containing very low-CP level gave significantly lower LBW than those fed high protein diet.…”
Section: Resultsmentioning
confidence: 77%